Maggot Therapy in Angiopathic Leg Ulcers: A Systematic Review and Meta-Analysis. (December 2018) - Siribumrungwong, Boonying; Wilasrusmee, Chumpon; Rerkasem, Kittipan
Maggot therapy (MT) is a biological debridement tool using blowfly larvae to digest necrotic tissue as its food. In addition, maggot secretion contains several peptides that has antibacterial effect and healing stimulants that might enhance wound healing. Clinical outcomes from previous meta-analyses demonstrated benefit of MT, but results were highly heterogeneous. We have conducted an updated systematic review and meta-analysis with clearly defined clinical outcomes according to mechanism of MT including successful debridement, healing rate, and time to heal. Furthermore, our study was the first meta-analysis that reported wound-related pain between MT and conventional therapy. MEDLINE and Scopus were searched for comparative studies of MT and conventional therapy. Ten studies were eligible, of which 5 studies were angiopathic (venous or mixed arteriovenous ulcers) and the other 5 were diabetic foot ulcer. The MT had significant higher rate of successful debridement with risk ratio of 2.3 (95% confidence interval = 1.7-3.0) with low heterogeneity. Time to heal was about 3.1 weeks (95% confidence interval = 1.2-5.0), significantly shorter in MT but with high heterogeneity. Healing rate and pain were not significantly different between groups with high heterogeneity. In conclusion, MT was an effective debridement tool compared with conventional therapy. More studies should be done to confirm other findings because of high heterogeneity.